Analisis Kesenjangan Regional di Sektor Pertanian Indonesia Tahun 2023 Melalui Pendekatan Cluster - Melynda Isaura; Fauzi Dwi Aryasatyawan; Sri Pingit Wulandari (International Forum of Researchers and Lecturers, 2024)
Indonesia is an agricultural country with great potential in the agricultural sector, both as a source of livelihood and as an economic driver. This sector has an important function in food security, improving farmers' welfare, and preserving the environment. Given Indonesia's regional diversity, it is important to develop policies that suit the agricultural characteristics of each region. This research uses the clustering method, a technique that groups data based on similar characteristics so that objects in one group (cluster) have high similarities, while between clusters they are different. This research applies the clustering method to group provinces in Indonesia based on agricultural sector factors in 2023, using hierarchical and non-hierarchical techniques. The results show that the optimum clusters obtained using both single linkage and K-Means formed five optimal clusters. The Java Island cluster shows high productivity, while Riau, East Kalimantan and North Kalimantan have quite high productivity with minimal labor. The largest clusters have a lot of unmanaged land, increasing employment opportunities. Significant variables influence grouping.